2007
DOI: 10.1590/s1677-55382007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in patients with chronic renal failure

Abstract: Objective: Determine the prevalence of erectile dysfunction in patients undergoing hemodialysis. Materials and Methods:This cross-sectional study was carried out to determine the prevalence of erectile dysfunction in a population of 58 patients in hemodialysis program. Erectile dysfunction was assessed by using the International Index of Erectile Function (IIEF). Information on demographic data, renal failure, comorbidities, laboratory tests and search for medical treatment for erectile dysfunction by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 19 publications
7
37
2
Order By: Relevance
“…The incidence is even higher in patients on chronic dialysis due to specific (5) and 83% in Saudi Arabia (6). Lower prevalence of ED has been reported in patients on dialysis living in Spain (7), Brazil (8), and Netherlands (9) (respectively 60%, 54.9%, and 69%). CIGOP in 1981 showed that more than 50% of male patients with CKD showed erectile dysfunction (10) The mild and moderate grades of ED, with a prevalence of respectively 28.8% and 27.4%, were the most represented severities in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence is even higher in patients on chronic dialysis due to specific (5) and 83% in Saudi Arabia (6). Lower prevalence of ED has been reported in patients on dialysis living in Spain (7), Brazil (8), and Netherlands (9) (respectively 60%, 54.9%, and 69%). CIGOP in 1981 showed that more than 50% of male patients with CKD showed erectile dysfunction (10) The mild and moderate grades of ED, with a prevalence of respectively 28.8% and 27.4%, were the most represented severities in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ED, four grades of severity were defined as follows: mild (score, 17-21); light (score, 12-16); moderate (score, [8][9][10][11]; and severe (score, 5-7)…”
Section: Methodsmentioning
confidence: 99%
“…This assumption was confirmed by the results of kidney transplants in early stage of CKD which seem to improve erectile dysfunction [31]. Yet, Messina et al, Ajina et al and Malekmakan et al reported no correlation between hemodialysis duration and the onset of erectile dysfunction [7,8,28].…”
Section: (B) Prevalence Of Erectile Dysfunctionmentioning
confidence: 92%
“…However, the low ED prevalence reported by Zbiti et al could be attributable to the young age of the study population (mean age = 45 ± 11.8 years) and the difference in methodology. [1,4,7,[20][21][22]27,29]. In fact, aging is a risk factor for occurrence of atherosclerosis.…”
Section: (B) Prevalence Of Erectile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation